The efficacy of intrapleural prolonged photodynamic therapy in female patient with malignant pleuritis - A. Kh. Trakhtenberg; V. V. Sokolov; E. V. Filonenko; O. V. Pikin; D. A. Vursol; K. I. Kolbanov; V. A. Glushko; G. P. Krylova (Biomedical Photonics, 2019)
Current approaches to diagnostics and treatment of patients with pleural metastases complicated by malignant pleuritis are reviewed. The method of intrapleural photodynamic therapy with photosens developed in P.A.Herzen MCRI for primary and metastatic pleural diseases complicated by malignant pleuritis is represented; for 66 patients there were good efficacy as pleurodesis in 92.4% of cases. The case of intrapleural photodynamic therapy in female patient with pleural mesothelioma complicated by malignant pleuritis with good short- and longterm results and significantly improved quality of life is reported.